Openness and innovation in online higher education: a historical review of the two discourses. (4th May 2021) - Lee, Kyungmee
ABSTRACT: This article tackles a critical question:'to what extent can online higher education (HE) be open and innovative at the same time?' To provide a more comprehensive answer to the question, the author takes up a notion of discourse and situates the analysis in a specific online HE setting: Athabasca University (AU), Canada. In this article, the author first unpacks how the openness and innovation discourses originally emerged in AU throughout its early years and how the original conceptualisation of the two and their relationships have shifted in more recent years. The results demonstrate that there has been an increasing level of discontinuity between the conceptualisation of openness and innovation as independent principles and the operationalisation of the two, incompatible in course design practice at AU. Being fully open to diverse student groups and being technologically innovative by integrating a state-of-the-art technology cannot be achieved in a single online course. In addition, being pedagogically innovative by increasing interactivity among students while maintaining the same level of flexibility provided by the independent study model seems very challenging. This article also discusses the institutional conditions that make teaching-oriented innovation more difficult to achieve.